An analysis of shariah non-compliant money : the management by baitulmal, Selangor Islamic Religious Council (MAIS) and Wilayah Persekutuan Islamic Religious Council (MAIWP) / Intan Nursyafiqah Mohd Safuan - Mohd Safuan, Intan Nursyafiqah (2019)
This paper presents the management of Shariah non-compliant money by baitulmal Selangor Islamic Religious Council (MAIS) and Wilayah Persekutuan Islamic Religious Council (MAIWP). The role of Baitulmal is marginalized as well diminished its function in small units at the State Islamic Religious Council. This caused the knowledge of the society about the Baitulmal still not clear even the basic roles of baitulmal still make people confused and blur. So relate with nowadays issue, illegal activities are increasing, in the middle time, people are aware about the Shariah non-complaint money that they own but they do not know ways to disposal it. So this paper is to analysis the management that have been done by MAIS and MAIWP on Shariah non-compliant money. This qualitative study is conducted using data collection methods and analysis of this data focuses on the process of the Shariah noncompliant manage by MAIS and MAIWP. Data obtained in the form of content analysis is analyzed using inductive, deductive and comparative studies to produce results. Findings shows that there are some differences and similarities between the management of Shariah noncompliant money by MAIS and MAIWP. This study also suggested that the financial record of acceptance and distribution of Shariah non-compliant money is needed to manage clearly so that it can disclosed to people clearly.